Heart Failure with Preserved Ejection Fraction and Sudden Death: How to Identify High Risk Patients? - Finkler, Bruno; Luiz Luz Leiria, Tiago; Fröemming Jr, Clovis; Pinos, Javier; Barros Zanotta, Danilo; Lapa Kruse, Marcelo; Martins Pires, Leonardo; Glotz de Lima, Gustavo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Background: Cardiac failure with preserved ejection fraction corresponds to half of the cardiac failure cases, having a similar prognosis to patients with reduced ejection fraction. Cardiac sudden death is responsible to about one quarter of the death on these patients. Despite some trials were intended to identify patients with a higher risk to these outcome, it is not already know: how we should proceed to stratify the risk of sudden death in this patients. Methods: To assess the profile of patients with cardiac sudden death and cardiac failure with preserved ejection fraction, we did a literature review, searching for the newer articles about the theme. Outcome: Several trials were published involving patients with divers characteristics that can help us to identify patients with a higher risk of sudden death. The publication of risk score demonstrated that would be possible to identify patients with a >10% risk of sudden death in 5 years, what would be equivalent to the risk of reduced ejection fraction patients eligible to implantable cardioverter-defibrillator (ICD) therapy. Trials with electrophysiological study and programmed ventricular stimulation showed a good strategy to identify low risk patients for future arrhythmic events. Conclusion: Sudden death must be a target of the therapy in the patients with preserved heart failure. Efforts should be done with the objective to identify higher risk patients and search for the better risk stratification strategy, and after that, the definition of the benefit or not, of the invasive therapy as ICD. Keywords: Sudden Death; Cardiac Faillure; Preserved Ejection Fraction;